Trends and Patterns of Antibiotics Use in China’s Urban Tertiary Hospitals, 2016–19 - Zhu, Yulei; Qiao, Yang; Dai, Rouli; Hu, Xin; Li, Xin (Frontiers in Pharmacology, 2021)
Objectives: This study aimed to identify the trends in antibiotics utilization and patients costs, evaluating the effect of the policy and exploring factors associated with the irrational use of antibiotics. Methods: Based on the Cooperation Project Database of Hospital Prescriptions, data were collected from 89 tertiary hospitals in 9 cities in China during 2016-2019. The study sample consisted of prescription records with antibiotics for 3,422,710 outpatient & emergency visits and 26,118,436 inpatient hospitalizations. Results: For outpatients, the proportion of treated with antibiotics declined from 14.72% to 13.92% significantly (p<0.01). The proportion of antibiotic costs for outpatients decreased from 5.79% to 4.45% significantly (p<0.01). For emergency patients, the proportion of treated with antibiotics increased from 39.31% to 43.45% significantly (p<0.01). The proportion of antibiotic costs for emergency patients decreased from 36.44% to 34.69%, with no significant change (p=0.87). For inpatients, the proportion of treated with antibiotics increased from 23.82% to 27.25% significantly (p<0.01). The proportion of antibiotic costs for outpatients decreased from 18.09% to 17.19% with no statistical significance (P=0.89). Other β-lactam antibacterials (1663.03 ten thousand DDD) far exceeded other antibiotics categories. Stablely ranked first, followed by Macrolides, lincosamide and streptogramins (965.74 ten thousand DDD), Quinolone antibacterials (710.42 ten thousand DDD), and β-lactam antibacterials, penicillins (497.01 ten thousand DDD). Conclusions: The proportion of treated with antibiotics for outpatients and inpatients meet the WHO standards. The antibiotics use varied by different survey areas, clinical departments, patient gender, patient age and antibiotics categories. More efforts should focus on improving the appropriateness of antibiotics use at the individual level.